(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
In this thesis, the modern mechanisms of management of cross-border e-commerce are revealed in content, highlighting its role in international trade and its role in the development of national economies. The rapid development of digital technologies and global coverage of the internet are setting the stage for the rise of cross-border e-commerce to a new level. In this regard, the thesis analyzes the relevance of the implementation of logistics systems based on modern technologies, mechanisms for the formation of electronic payment and security systems, digitization of customs processes and real-time monitoring in the management of e-commerce. Also highlighted are mechanisms to ensure effective cooperation between the public and private sectors involved in cross-border e-commerce, rational use of international e-commerce platforms and integration of domestic manufacturers into global e-commerce systems. The results of the study indicate that the formation of effective mechanisms for managing cross-border e-commerce will be an important factor in increasing the competitiveness of the national economy, strengthening export potential and creating new jobs. The results of the thesis can be applied practically in the development of e-commerce strategies.